2015
DOI: 10.1097/01.sa.0000459233.90479.71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cognitive Aid on Adherence to Perioperative Assessment and Management Guidelines for the Cardiac Evaluation of Noncardiac Surgical Patients

Abstract: BACKGROUND-The 2007 American College of Cardiologists/American Heart Association Guidelines on Perioperative Cardiac Evaluation and Care for Noncardiac Surgery is the standard for perioperative cardiac evaluation. Recent work has shown residents and anesthesiologists do not apply these guidelines when tested. This research hypothesized that a decision support tool would improve adherence to this consensus guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…6,7 The use of DSTs has been shown to enhance compliance with guidelines, protocols, and best practices as well as improve outcomes in both simulation and direct patient care. [8][9][10][11][12][13][14][15] Electronic DSTs (eDSTs) in particular, due to their flexibility and integration into clinician workflow, have shown success in improving care by increasing adherence to published guidelines and protocols. [10][11][12][13][14][15][16] Because smartphones are rapidly becoming integral to physicians, and smartphone applications (apps) are becoming more commonplace, the app platform becomes a logical modality for an eDST to be used as a supplement to printed guidelines.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 The use of DSTs has been shown to enhance compliance with guidelines, protocols, and best practices as well as improve outcomes in both simulation and direct patient care. [8][9][10][11][12][13][14][15] Electronic DSTs (eDSTs) in particular, due to their flexibility and integration into clinician workflow, have shown success in improving care by increasing adherence to published guidelines and protocols. [10][11][12][13][14][15][16] Because smartphones are rapidly becoming integral to physicians, and smartphone applications (apps) are becoming more commonplace, the app platform becomes a logical modality for an eDST to be used as a supplement to printed guidelines.…”
mentioning
confidence: 99%
“…19 The document is 31 pages long, and as with other guidelines, correctly applying these recommendations to clinical situations can often be a challenge. 8,20 However, our group has shown that these guidelines and others can be presented in smartphone app form and that use of such apps improves the adherence to guidelines in simulated clinical encounters. 8,20,21 As such, understanding the actual real-world use of guideline apps is needed to guide medical specialties and component societies in the ongoing development and distribution of clinical practice guidelines.…”
mentioning
confidence: 99%
See 1 more Smart Citation